Occurrence Mechanism of Roof-Fall Accidents in Large-Section Coal Seam Roadways and Related Support Design for Bayangaole Coal Mine, China - Shitan Gu; Bangyou Jiang; Gensheng Wang; Huabin Dai; Mingpeng Zhang (Advances in Civil Engineering)
This study focused on large-scale roof-fall accidents occurred in large-section coal seam roadways of Bayangaole Coal Mine, Inner Mongolia, China, and investigated the occurrence mechanism of roof-fall and the related supporting control method in detail. Firstly, the fracture characteristics of the surrounding rocks on the roadway roof were measured using a stratum detector. The results showed that the roadway roof underwent the most severe failure with a maximum deformation of 3.53 m; the bedding separation and fracture zones were distributed at irregular intervals. Accordingly, the entire stratum was separated into several thin sublayers, significantly reducing the stability of roof. In addition, the roof medium grained sandstone of roadway is water-rich strata, and water aggravates the damage of roof. Next, the mechanism of the occurrence of roof-fall accidents in the roadway was elucidated in detail. The following three reasons are mainly attributed to the occurrence of roof-fall accidents: (i) effects of mining-induced stress and tectonic stress, (ii) existence of equipment cavern on the side of roadway, and (iii) unreasonable support parameters. On that basis, a new supporting design is proposed, including a more reasonable arrangement of anchor cables and bolts, bolts with full-length anchorage which are applicable in cracked and water-rich roadway, high-strength anchor cables, and crisscrossed steel bands. Moreover, high pretightening force was applied. Finally, a field test was performed, and the mining-induced roof displacement and stress on anchor cable (bolt) were monitored in the test section. The maximum roof displacements at the two monitoring sections were 143 mm and 204 mm, respectively, far smaller than the roadway’s allowable deformation. Moreover, the stress on roof anchor cables (bolts) was normal, and no anchorage-dragging and tensile failure phenomena were observed. The monitoring data indicated that the new supporting design was remarkable on the control of large-section coal seam roadway roof deformation.